Outer surface protein C is a dissemination-facilitating factor of Borrelia burgdorferi during mammalian infection. - Sunita V Seemanapalli; Qilong Xu; Kristy McShan; Fang Ting Liang (PLoS ONE, 2010)
The Lyme disease spirochete Borrelia burgdorferi dramatically upregulates outer surface protein C (OspC) in response to fresh bloodmeal during transmission from the tick vector to a mammal, and abundantly produces the antigen during early infection. As OspC is an effective immune target, to evade the immune system B. burgdorferi downregulates the antigen once the anti-OspC humoral response has developed, suggesting an important role for OspC during early infection.In this study, a borrelial mutant producing an OspC antigen with a 5-amino-acid deletion was generated. The deletion didn't significantly increase the 50% infectious dose or reduce the tissue bacterial burden during infection of the murine host, indicating that the truncated OspC can effectively protect B. burgdorferi against innate elimination. However, the deletion greatly impaired the ability of B. burgdorferi to disseminate to remote tissues after inoculation into mice.The study indicates that OspC plays an important role in dissemination of B. burgdorferi during mammalian infection.